2004
DOI: 10.1111/j.1365-2362.2004.01312.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism assessed by 125I‐iodophenyl 9‐methylpentadecanoic acid (9MPA) and expression of fatty acid utilization enzymes in volume‐overloaded hearts

Abstract: These data suggest that myocardial fatty acid metabolism is enhanced in eccentric cardiac hypertrophy by volume-overload without changes in protein expressions of PPARalpha and fatty acid utilization enzymes. Our data may provide a novel insight into the subcellular mechanisms for the pathological process of cardiac remodelling in response to mechanical stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…After injection, planar images were obtained followed by single photon emission computed tomography (SPECT) images 3 hours. All images were acquired in the resting state us- ing a dual-head rotating gamma camera (Toshiba, Tokyo, Japan) [15][16][17] . Energy discrimination was provided by a 15% window centered on the 140 keV photopeak.…”
Section: Methodsmentioning
confidence: 99%
“…After injection, planar images were obtained followed by single photon emission computed tomography (SPECT) images 3 hours. All images were acquired in the resting state us- ing a dual-head rotating gamma camera (Toshiba, Tokyo, Japan) [15][16][17] . Energy discrimination was provided by a 15% window centered on the 140 keV photopeak.…”
Section: Methodsmentioning
confidence: 99%
“…[30][31][32] Miyamoto et al, measured the expression of several enzymes involved in FA metabolism and found that the levels of PPARα, a key transcriptional regulator of metabolic genes were normal in volume-overloaded hypertrophied rabbit hearts. 33 In addition, several studies have reported normal FA uptake, metabolism and carnitine palmitoyltransferase 1 activity, the rate limiting enzyme in mitochondrial beta-oxidation, in cardiac hypertrophy. 30,32 Our findings suggest that the cardiac hypertrophy caused by loss of Cav1 gene expression in cardiac fibroblasts was not severe enough to trigger a switch in myocardial energy metabolism commonly observed in pressure-or volume-overload induced hypertrophy and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…It may facilitate switching of substrate utilization. In the rabbit model of volume overload hypertrophic heart failure there was no downregulation in PPAR-␣ protein expression or in the expression of enzymes of fatty acid oxidation, but the uptake and oxidation of fatty acids was increased [61]. In a rat infarction model of heart failure a significant decrease in mRNA expression of PPAR-␣ was …”
Section: Effects On Oxidative Phosphorylationmentioning
confidence: 91%